Mình cần gấp. Mong các bạn giúp đỡ
Đặt \(A=\frac{5^{28}+5^{24}+.........+5^4+1}{5^{30}+5^{28}+5^{26}+.....+5^2+1}=\frac{B}{C}\)
Xét tử \(B=5^{28}+5^{24}+........+5^4+1\)
\(\Rightarrow5^4.B=5^{32}+5^{28}+........+5^8+5^4\)
\(\Rightarrow625.B=5^{32}+5^{28}+........+5^8+5^4\)
\(\Rightarrow625.B-B=624.B=5^{32}-1\)
\(\Rightarrow B=\frac{5^{32}-1}{624}\)
Xét mẫu \(C=5^{30}+5^{28}+5^{26}+........+5^2+1\)
\(\Rightarrow5^2.C=5^{32}+5^{30}+5^{28}+.........+5^4+5^2\)
\(\Rightarrow25.C=5^{32}+5^{30}+5^{28}+........+5^4+5^2\)
\(\Rightarrow25.C-C=24.C=5^{32}-1\)
\(\Rightarrow C=\frac{5^{32}-1}{24}\)
\(\Rightarrow A=\frac{B}{C}=\frac{5^{32}-1}{624}:\frac{5^{32}-1}{24}=\frac{5^{32}-1}{624}.\frac{24}{5^{32}-1}=\frac{24}{624}=\frac{1}{26}\)
Đặt \(B=5^{28}+5^{24}+...+5^4+1\Rightarrow5^4B=5^{32}+5^{28}+...+5^8+5^4\)
\(\Rightarrow\left(5^4-1\right)B=5^{32}-1\Rightarrow B=\frac{5^{32}-1}{5^4-1}\)
Đặt \(C=5^{30}+5^{28}+...+5^2+1\Rightarrow5^2C=5^{32}+5^{30}+...+5^4+5^2\)
\(\Rightarrow\left(5^2-1\right)C=5^{32}-1\Rightarrow C=\frac{5^{32}-1}{5^2-1}\)
Khi đó \(A=\frac{B}{C}=\frac{\frac{5^{32}-1}{5^4-1}}{\frac{5^{32}-1}{5^2-1}}=\frac{5^2-1}{5^4-1}=\frac{1}{26}\)
Vậy................